A formação continuada dos professores: desafio dos coordenadores pedagogicos de Mairiporã - Matsukuma, Luciana (2021)
Motivation for doing the research discussed in this paper originated from concerns and reflections about teachers’ continuous training, especially when school-centered, which has the pedagogical coordinator as trainer, through the eyes of teachers’ professional development. Research main objective is to understand the conceptions followed by Pedagogical Coordinators and Pedagogical Support Teachers, who work in the city of Mairiporã, to develop continuous training with their groups of teachers, while investigating how they have been performing training moments, as well as which are the main challenges they face as trainers. The study relied on the participation of eight Pedagogical Coordinators (PCs) and Pedagogical Support Teachers (PSTs) working in the public educational system of the city of Mairiporã. Participants’ selection criteria considered the four individuals with the longest experience and the four individuals with the shortest experience in their jobs, besides the availability to take part in the research. Theoretical base is grounded in the productions of Marcelo (1999), Nóvoa (1997, 2008), Schön (2000), Imbernón (2004, 2009, 2011), Gatti e Barreto (2009), Canário (1994, 1998), Alarcão (1996, 2001), Almeida (2018), Cunha, (2006), Gouveia and Placco (2015), Placco, Almeida and Souza (2011, 2019), Placco and Souza (2015) and Silva (2019). Investigation followed qualitative approach, and data was collected through a discussion group, which was based on Meinerz (2011) and Weller (2006). Data analysis was inspired in the base of Prose Analysis, by André (1983). Data were, then, organized and categorized around three themes: being a coordinator; PC’s trainer role; Challenges of the job. Results showed that PCs and PSTs from Mairiporã acknowledge themselves as teacher trainers who promote training moments that consider teachers’ knowledge and who recognize that teachers are producers of knowledge themselves, while promoting reflections over pedagogical practices, sharing practices, and searching for joint solutions for school demands. We also realized that, although PCs and PSTs have dialogical, reflexive, and dynamical practices, they still rely on structural and technical training models, idealized by specialists, which evidence traces of authoritarian trainings based on a conservative paradigm of technical rationality. PCs’ and PSTs’ challenges in developing continuous trainings are lack of specific training for the job, work overload and older teachers’ resistance to change and transform their practices which have been crystalized by time. Research results could contribute with the Department of Education of Mairiporã in the elaboration of training paths for PCs and PSTs, based on the demands presented in this study